Construction of Novel Yeast Strains from Candida tropicalis KBKTI 10.5.1 and Saccharomyces cerevisiae DBY1 to Improve the Performance of Ethanol Production Using Lignocellulosic Hydrolysate - Jamaluddin; Eny Ida Riyanti; Nisa Rachmania Mubarik; Edy Listanto (Tropical Life Sciences Research, 2023)
Increased consumption of xylose-glucose and yeast tolerance to lignocellulosic hydrolysate are the keys to the success of second-generation bioethanol production. Candida tropicalis KBKTI 10.5.1 is a new isolated strain that has the ability to ferment xylose. In contrast to Saccharomyces cerevisiae DBY1 which only can produce ethanol from glucose fermentation. The research objective is the application of the genome shuffling method to increase the performance of ethanol production using lignocellulosic hydrolysate. Mutants were selected on xylose and glucose substrates separately and using random amplified polymorphic DNA (RAPD) analysis. The ethanol production using lignocellulosic hydrolysate by parents and mutants was evaluated using a batch fermentation system. Concentrations of ethanol, residual sugars, and by-products such as glycerol, lactate and acetate were measured using HPLC machine equipped with Hi-plex H for carbohydrate column and a refraction index detector (RID). Ethanol produced by Fcs1 and Fcs4 mutants on acid hydrolysate increased by 26.58% and 24.17% from parent DBY1, by 14.94% and 21.84% from parent KBKTI 10.5.1. In contrast to the increase in ethanol production on alkaline hydrolysate, Fcs1 and Fcs4 mutants only experienced an increase in ethanol production by 1.35% from the parent KBKTI 10.5.1. Ethanol productivity by Fcs1 and Fcs4 mutants on acid hydrolysate reached 0.042 g/L/h and 0.044 g/L/h. The recombination of the genomes of different yeast species resulted in novel yeast strains that improved resistance performance and ethanol production on lignocellulosic hydrolysates.